Preparing semen slides in cases of sexual assault: Do they who smear first smear best?. (April 2021) - Nittis, Maria; Cochrane, Clint; Hughes, Rod; Franco, Michele
Abstract: When providing a forensic assessment for a victim of sexual assault, a smear is made from any swab that has been collected with the purpose of finding sperm. A smear is made to assist the laboratory identify the optimal swab for DNA testing, to aid in the selection of downstream DNA testing options, to evaluate morphology and quantity of sperm in order to provide time since intercourse assessments, and to contribute additional information to the crime scene case when trying to determine how an offender's DNA came to be at the site where it was located. In the majority of Australian states, the forensic examiner makes the smear at the time of the forensic assessment (forensic history, examination, collection of specimens, documentation of injury and prophylactic treatment for sexually transmitted infections and pregnancy). The smear could be made, however, at a later time by forensic laboratory staff. There are some jurisdictions (for example in Queensland, Australia) where this is the preferred process. This research paper compared smear preparation by the forensic examiner with that prepared, at a later time, by the laboratory scientist. 143 pairs of high vaginal smears were analysed over a two and a half year period. Smears made by the examiner contained, for the most part, higher numbers of sperm, more background material and more intact sperm than smears made at a later date by laboratory scientific staff. Highlights: Preparation of semen slides in cases of sexual assault. Most slides in this study, whether prepared by the examiner or at the lab, were negative for sperm (>70%). Examiner prepared slides have more sperm and allow for more discriminating time since intercourse estimates than lab prepared slides.